2007
DOI: 10.2174/157016207779316323
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Proline at Position 7 of the HIV-1 Spacer Peptide p1 Suppresses Viral Infectivity in a Strain Dependent Manner

Abstract: The HIV-1 spacer peptide p1 is located in the C-terminus of the Gag polyprotein and separates the nucleocapsid (NC) and p6(Gag). Research centered on p1 has been limited and as yet no function has been ascribed to this spacer peptide. We have previously found that the conserved p1 proline residues (position 7 and 13) are critical for replication in the HIV-1 strain HXB2-BH10. In this study we have focused on the proline rich p1-p6(Gag) C-terminus of HIV-1. We individually examined the role of p1 proline's in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…1b) [2,7]. Mutations in this region, particularly the proline residues at positions 7 and 13, negatively affect protein processing, RNA dimer stability and abolish viral infectivity in multiple strains of HIV-1 [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1b) [2,7]. Mutations in this region, particularly the proline residues at positions 7 and 13, negatively affect protein processing, RNA dimer stability and abolish viral infectivity in multiple strains of HIV-1 [7].…”
Section: Introductionmentioning
confidence: 99%
“…1b) [2,7]. Mutations in this region, particularly the proline residues at positions 7 and 13, negatively affect protein processing, RNA dimer stability and abolish viral infectivity in multiple strains of HIV-1 [7]. Although the role of p1 in viral replication is not well understood, it has been suggested that mutations in p1 impact nucleocapsid function, which is important in the early stages of reverse transcription and integration [7].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is present in both gag and pol open reading frames. Mutations (e.g., P at position 7) can affect processing, RNA dimer stability, and infectivity (Hill et al, 2007). Mutations in Gag SP2 may affect nucleocapsid function, particularly in early stages of reverse transcription and integration, yet SP2 appears to play a minor role in viral infectivity (de Marco et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis studies suggest a possible implication of its proline residues in the processing of Gag polyprotein, the control of gRNA dimer stability and the packaging of Gag-Pol into nascent virions. These mutations also abolish the infectivity of multiple HIV-1 strains in peripheral blood monolayer cells [213]. While the proper processing between NC and p6 appears crucial for viral infectivity and maturation, the SP2 itself seems dispensable, and its deletion has only minor effect on the viral infectivity [214].…”
Section: Spacer Peptide (Sp1) and Sp2 Domains Of Hiv-1 Gagmentioning
confidence: 99%